2014
DOI: 10.1111/cobi.12358
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for enforcement costs in the spatial allocation of marine zones

Abstract: Marine fish stocks are in many cases extracted above sustainable levels, but they may be protected through restricted-use zoning systems. The effectiveness of these systems typically depends on support from coastal fishing communities. High management costs including those of enforcement may, however, deter fishers from supporting marine management. We incorporated enforcement costs into a spatial optimization model that identified how conservation targets can be met while maximizing fishers' revenue. Our mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 48 publications
(64 reference statements)
2
42
0
Order By: Relevance
“…The costs associated with surveillance and enforcement depend on both the size of the zones and the social and economic characteristics of the resource users. Only a few studies have explicitly quantified these costs (Ban and Klein 2009;Davis et al 2015). Ban et al (2011) compared the enforcement costs for staffing an entirely no-take protected area versus a mixed zone seascape (protected and fished) and found that compliance staffing was doubled when mixed zoning occurred.…”
Section: Costsmentioning
confidence: 99%
“…The costs associated with surveillance and enforcement depend on both the size of the zones and the social and economic characteristics of the resource users. Only a few studies have explicitly quantified these costs (Ban and Klein 2009;Davis et al 2015). Ban et al (2011) compared the enforcement costs for staffing an entirely no-take protected area versus a mixed zone seascape (protected and fished) and found that compliance staffing was doubled when mixed zoning occurred.…”
Section: Costsmentioning
confidence: 99%
“…), enforcement (Davis et al . ) and opportunity costs reflecting lost revenue (Klein et al . ; Ruiz‐Frau et al .…”
Section: Introductionmentioning
confidence: 99%
“…(Roberts et al., ). Accessibility for fishing and recreation may be more difficult, and dispersed MPAs require greater enforcement effort (Davis, Kragt, Gelcich, Schilizzi, & Pannell, ; Kritzer, ). Alternatively, a few large MPAs could have disproportionate spatial impacts on fishing communities (Halpern et al., ).…”
Section: Discussionmentioning
confidence: 99%